DAMPAK KEBIJAKAN LARANGAN EKSPOR ROTAN MENTAH TERHADAP INDUSTRI FURNITUR ROTAN INDONESIA 2011-2012 - Satria, Yudi; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper aims to analyze the impact of the ban policy on the export ofraw rattan towards Indonesian rattan furniture industry. Indonesian supplied theworld raw materials for 75.5%. Indonesia has the advantage in the production ofrattan raw materials, otherwise rattan furniture industry has not yet evolved.Through Permendag No. 35/M-DAG/PER/11/2011, Indonesia protect the rattanfurniture industry. In addition, this study aims to give information about thecondition of Indonesian rattan furniture industry before and after the issuance ofthe policy.This study applies mercantilism perspective. Mercantilism assume thateconomy controlled by political community and especially the government orcountry. Economic dependence on other countries for the mercantile should beavoided. When there is a threat of foreign parties in the free trade, then the statecan provide protection to avoid the impact. Protection theory used to analyze theimpact of the ban policy on the export of raw rattan towards Indonesian rattanfurniture industry. This study applies qualitative research method with libraryresearch.The results of this research founds that the ban policy on the raw rattanexport gives the positives influence on increases the export value of rattanfurniture and an increases in foreign exchange.Keywords: Mercantilism, Protection Policy, Rattan, Value of exports